2009
DOI: 10.1093/sleep/32.12.1579
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Compression Increases Upper Airway Collapsibility During Sleep in Obese Male Obstructive Sleep Apnea Patients

Abstract: Abdominal compression negatively impacts on UA collapsibility during sleep and this effect may help explain strong associations between central obesity and obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…This means that individuals succeeded in decreasing their abdominal fat. It has been reported that abdominal fat, BMI and NC are significant clinical predictors of OSAS [26,27]. NC has been suggested to be more predictive of OSAS than general obesity and the lack of impact on overall OSAS severity could be related to lack of significant difference in the change in NC [28].…”
Section: Discussionmentioning
confidence: 99%
“…This means that individuals succeeded in decreasing their abdominal fat. It has been reported that abdominal fat, BMI and NC are significant clinical predictors of OSAS [26,27]. NC has been suggested to be more predictive of OSAS than general obesity and the lack of impact on overall OSAS severity could be related to lack of significant difference in the change in NC [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, neck circumference also reflects central fat distribution. Centrally distributed fat has detrimental effects on thoraco-pulmonary mechanics 35 and upper airway collapsibility, 36 particularly in recumbent positions, increasing the effort breathing, 35 and may favor mouth opening during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in lung volume potentially reduces the degree of caudal traction exerted on the UA, and promotes UA collapse. Support for this interaction can be found in a study where abdominal compression during sleep in OSA patients worsened UA collapse [8]. The effect of abdominal obesity on UA function may be most evident in the supine posture and during sleep, particularly at the wake-sleep transition when other compensatory mechanisms become diminished.…”
Section: Airway Structural Challenges Of Osa and Momentioning
confidence: 91%